2005
DOI: 10.1111/j.1523-1755.2005.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma, urine, and renal expression of adiponectin in human systemic lupus erythematosus

Abstract: Plasma adiponectin levels are increased in patients with renal SLE compared to healthy controls and patients with nonrenal SLE. During renal but not nonrenal SLE flare, urine adiponectin levels increase significantly. Urine adiponectin may be a biomarker of renal SLE flare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
129
2
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(148 citation statements)
references
References 28 publications
10
129
2
6
Order By: Relevance
“…In our study, there was significantly higher serum adiponectin level among SLE patients with LN compared to SLE patients without LN, this is in agreement with Rovin et al study in 2005 27 , who demonstrated that plasma adiponectin levels are increased in patients with renal SLE compared to healthy controls and patients with non renal SLE.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In our study, there was significantly higher serum adiponectin level among SLE patients with LN compared to SLE patients without LN, this is in agreement with Rovin et al study in 2005 27 , who demonstrated that plasma adiponectin levels are increased in patients with renal SLE compared to healthy controls and patients with non renal SLE.…”
Section: Discussionsupporting
confidence: 82%
“…Our study showed significantly higher urinary adiponectin level in SLE patients when compared to controls and significantly higher urinary adiponectin level among SLE patients with LN when compared to patients without LN, this is concided with Rovin et al study in 2005 27 , who stated that urine adiponectin levels increased significantly with renal flare, but not non renal SLE flare.…”
Section: Discussionsupporting
confidence: 79%
“…A recent report showed that CTRP1 prevents collagen-induced platelet aggregation by specifically blocking von Willebrand's factor (vVW) binding to collagen [8]. In this study, we showed that CTRP1 is expressed in podocytes but not in endothelial cells or smooth muscle cells of the intrarenal arteries/arterioles, or in the endothelium of the glomerular and peritubular capillaries in the normal kidney [2]. In addition, CTRP1 expression is attenuated in the podocytes of an animal model of glomerulosclerosis.…”
Section: Discussionmentioning
confidence: 50%
“…Plasma and urine adiponectin levels appear to be increased in patients with SLE, especially in those with inflammatory glomerulonephritis (61). Interestingly, full-length (containing all isoforms) but not globular adiponectin induced IL-8 and monocyte chemoattractant protein 1 in microvascular endothelial cells and monocytes (62).…”
Section: Adipokines In Other Rheumatic Diseasesmentioning
confidence: 99%